2021
DOI: 10.1051/0004-6361/202140958
|View full text |Cite
|
Sign up to set email alerts
|

The period-gap cataclysmic variable CzeV404 Her: A link between SW Sex and SU UMa systems

Abstract: Context. We present a new study of the eclipsing cataclysmic variable CzeV404 Her (Porb = 0.098 d) that is located in the period gap. Aims. This report determines the origin of the object and the system parameters and probes the accretion flow structure of the system. Methods. We conducted simultaneous time-resolved photometric and spectroscopic observations of CzeV404 Her. We applied our light-curve modelling techniques and the Doppler tomography method to determine the system parameters and analyse the struc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
3
4
0
Order By: Relevance
“…Since Jacobian has a strong dependence on the radius (∝ r −3 ), an omission of Jacobian gives a biased impression that the emission from the outer disk much exceeds that from the inner disk. We note that the same issue has already been pointed out by Kato (2021) in figure 12 of Kára et al (2021). In figure A1, we show the copied Doppler map of Hα of Neustroev et al (2016) A.1.3 double-humped profile in quiescence of WZ Sge-type dwarf novae Amantayeva et al (2021) showed that the double-humped orbital profile of EZ Lyn in quiescence can be explained with a spiral arm structure in an accretion disk reaching the 2:1 resonance radius.…”
Section: A12 Jacobian In Conversion From Doppler Tomography To Spacia...supporting
confidence: 68%
See 1 more Smart Citation
“…Since Jacobian has a strong dependence on the radius (∝ r −3 ), an omission of Jacobian gives a biased impression that the emission from the outer disk much exceeds that from the inner disk. We note that the same issue has already been pointed out by Kato (2021) in figure 12 of Kára et al (2021). In figure A1, we show the copied Doppler map of Hα of Neustroev et al (2016) A.1.3 double-humped profile in quiescence of WZ Sge-type dwarf novae Amantayeva et al (2021) showed that the double-humped orbital profile of EZ Lyn in quiescence can be explained with a spiral arm structure in an accretion disk reaching the 2:1 resonance radius.…”
Section: A12 Jacobian In Conversion From Doppler Tomography To Spacia...supporting
confidence: 68%
“…Since Jacobian has a strong dependence on the radius (∝ r −3 ), an omission of Jacobian gives a biased impression that the emission from the outer disk much exceeds that from the inner disk. We note that the same issue has already been pointed out byKato (2021) in figure12ofKára et al (2021). In figureA1, we show the copied Doppler map of Hα of Neustroev et al (2016) using data observed in 2005 (upper left-hand panel).…”
supporting
confidence: 64%
“…It could also provide insights on how the system changes during the small flares appearing during quiescence. Additionally, such spectra would permit a similar analysis to what what was done by Kára et al (2021), who used Doppler tomography (Marsh & Horne 1988) on the disc emission lines to obtain information on the velocity structure of the disc. Moreover, new spectra, especially in UV, could also help elucidate the nature of the primary and secondary.…”
Section: Discussionmentioning
confidence: 93%
“…To do this, we attempt to reproduce the collected photometric observations of the system eclipse light curves in quiescence, standstill, and during an outburst using the tool developed by Zharikov et al (2013). The detailed description of the model can be found in our recent papers of Subebekova et al (2020) and Kára et al (2021). Here we note only that the light curve is a superposition of the flux contribution of four main components: the white dwarf primary, the secondary star, and the accretion disk with the bright spot formed at the disk/ stream impact region.…”
Section: Eclipse Light-curve Modeling and System Parametersmentioning
confidence: 99%
“…The disk limb darkening also includes the following Eddington approximation (Mayo et al 1980;Paczynski & Schwarzenberg-Czerny 1980). We also used the complex model for the bright spot described in detail in Kára et al (2021; see Figure 9 therein) where all definitions of parameters can be found.…”
Section: Eclipse Light-curve Modeling and System Parametersmentioning
confidence: 99%